FlyORF-TaDa allows rapid generation of new lines for in vivo cell-type-specific profiling of protein–DNA interactions in Drosophila melanogaster. Issue 1 (22nd December 2020) - Aughey, Gabriel N; Delandre, Caroline; McMullen, John P D; Southall, Tony D; Marshall, Owen J
Abstract: Targeted DamID (TaDa) is an increasingly popular method of generating cell-type-specific DNA-binding profiles in vivo . Although sensitive and versatile, TaDa requires the generation of new transgenic fly lines for every protein that is profiled, which is both time-consuming and costly. Here, we describe the FlyORF-TaDa system for converting an existing FlyORF library of inducible open reading frames (ORFs) to TaDa lines via a genetic cross, with recombinant progeny easily identifiable by eye color. Profiling the binding of the H3K36me3-associated chromatin protein MRG15 in larval neural stem cells using both FlyORF-TaDa and conventional TaDa demonstrates that new lines generated using this system provide accurate and highly reproducible DamID-binding profiles. Our data further show that MRG15 binds to a subset of active chromatin domains in vivo . Courtesy of the large coverage of the FlyORF library, the FlyORF-TaDa system enables the easy creation of TaDa lines for 74% of all transcription factors and chromatin-modifying proteins within the Drosophila genome.